PROSEDUR LELANG HAK TANGGUNGAN DI KOPERASI SIMPAN PINJAM INTIDANA CABANG JAKARTA PUSAT - Vina Islami (Cakrawala - Jurnal Humaniora, 2017)
The Union is one of the non banking financial institution that is intended for small – medium enterprises. When the lending on, union always obliges the members as a debitor to provide such a guarantee in the form of Mortgage. With the guarantee, Union as a creditor can get top priority (prefernce) for the re-payment of loan when the debtor get breach of contract. This research will be studied about auction procedure of mortgage by Credit Union Intidana Branch Office In Central Jakarta and the fulfillment of the rights of the parties. This descriptive analytical research use empirical juridical approach and data obtained through literary research and field research. Further more, the data were analyzed qualitatively. The auction process to the mortgage object in Credit Union Intidana is done through the state auction agency under Directorate General of Receivables and state auction supervision. To be able to conduct auction in the Directorate General of Receivables and state auction, Credit Union Intidana aplly for auction to through the office of Country Financial Service and Auction, Then from the results of the auction, the fullfilment of the rights of the parties carried out of the auction results larger than obligation debtors or owner of the security rights object. In case defeciency, then lack of it will be made write off to debtors liabilty by the union.   Keywords : Auction, Mortgage